Telecollaboration and willingness to communicate in English of secondary school students - Napiórkowska, Marta (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study aimed to explore a possible relationship between secondary students’ perceptions of willingness to speak English in situations outside the classroom and their participation in a telecollaboration project held in English as lingua franca. 22 Spanish, 26 Polish and 14 Romanian students participated in the research. The data was collected through an online questionnaire, administered to the students before and after the telecollaboration. The findings reveal that audio-visual and synchronous telecollaboration has a positive impact on the willingness to speak English outside the classroom with other users of the same language